Linear Aliphatic Dimeric Esters from Cork Suberin - Graça, José; Santos, Sara (Biomacromolecules, 2006)
Cork suberin was partially depolymerized by methanolysis catalyzed by calcium hydroxide. Analysis by GC-MS of the methanolysate showed suberin monomers, including glycerol and long-chain α,?-diacids and ?-hydroxyacids. ESI-MS analysis of the methanolysate showed, besides the aliphatic monomers, suberin oligomers, including linear dimeric esters of α,?-diacids and ?-hydroxyacids. Two types of dimeric esters were identified:? a α,?-diacid linked to a ?-hydroxyacid and two inter-linked ?-hydroxyacids. The α,?-diacids and ?-hydroxyacids found as monomer residues in the dimeric esters were mainly the C18 monomers with midchain substituents. The identification of these dimeric esters was based in their CID-MS/MS spectra and confirmed after synthesis of model compounds. The occurrence of inter-esterified long-chain monomers in suberin brings a new insight in the understanding of the polyester structure of this biopolymer.
From Duplicate 1 (Linear Aliphatic Dimeric Esters from Cork Suberin - Graça, José; Santos, Sara)
Keywords: cork suberin; dimeric esters; Dimerization; Electrospray Ionization; Electrospray Ionization: metho; Esters; Esters: chemistry; GC-MS (voyant); Lipids; Mass; Membrane Lipids; Membrane Lipids: chemistry; Molecular Structure; Sensitivity and Specificity; Spectrometry; Trees; Trees: chemistry

Antimutagenicity of a suberin extract from Quercus suber cork. - Krizková, L; Lopes, M H; Polónyi, J; Belicová, a; Dobias, J; Ebringer, L (Mutation research, 1999)
The possible protective effect of a suberin extract from Quercus suber cork on acridine orange (AO)-, ofloxacin- and UV radiation-induced mutagenicity (bleaching activity) in Euglena gracilis was examined. To our knowledge, the present results are the first attempt to analyse suberin in relation to mutagenicity of some chemicals. Suberin exhibits a significant dose-dependent protective effect against AO-induced mutagenicity and the concentration of 500 micrograms/ml completely eliminates the Euglena-bleaching activity of AO. The mutagenicity of ofloxacin is also significantly reduced in the presence of suberin (125, 250 and 500 micrograms/ml). However, the moderate protective effect of suberin on UV radiation-induced mutagenicity was observed only at concentrations 500 and 1000 micrograms/ml. Our data shows that suberin extract from Q. suber cork possess antimutagenic properties and can be included in the group of natural antimutagens acting in a desmutagenic manner.
Keywords: Acridine Orange; Acridine Orange: toxicity; Animals; Antimutagenic Agents; Antimutagenic Agents: pharmacology; Euglena gracilis; Euglena gracilis: drug effects; Euglena gracilis: genetics; Euglena gracilis: radiation effects; Lipids; Membrane Lipids; Membrane Lipids: pharmacology; Mutagenicity Tests; Mutagenicity Tests: methods; Mutagens; Mutagens: toxicity; Ofloxacin; Ofloxacin: toxicity; Plant Extracts; Plant Extracts: pharmacology; Plant Shoots; Plant Shoots: chemistry; Spectrophotometry, Ultraviolet; Superoxides; Superoxides: metabolism; Trees; Trees: chemistry; Ultraviolet Rays